Effect of Germination on Proximate Composition of Amaranth Seeds (Amaranth Cruentus) - Paudel, Sajana; Khadka, Abhishek; Koirala, Ujjwal; Khanal, Hari (Journal of Food Science and Technology Nepal, 2022)
Effects on proximate composition of amaranth during germination were studied. Amaranth grains were geminated during 48 hours at ambient condition was subjected to proximate analysis. Germination of amaranth for 48 hours had a significant effect on nutritional factors. On proximate composition, protein content and carbohydrate content were found to be increased from 18.13 to 20.53% and 54.2 to 55.5% respectively but not increased significantly whereas Similarly crude fat, crude fiber & total ash significantly decreased from 9.66 to 7.07%, 4.01 to 3.96%, and 54.5 to 55.5% respectively on dry basis.